Modeling results of a new high performance free liquid piston engine. (15th January 2023) - Chouder, Ryma; Benabdesselam, Azzedine; Stouffs, Pascal
Abstract: Free piston engines, Ericsson hot air engines and liquid piston machines are concepts which, each independently, are considered highly relevant. These technologies have been associated to design a Free Liquid Piston Ericsson Engine (FLPEE). Both ends of a U-tube partly filled with water are equipped with valves. Air is the working fluid. One leg of the U-tube acts to compress the air, while the other arm allows the expansion of the compressed air previously heated by the hot source of the engine. This free liquid piston system is coupled with a micro-expander. A dynamic model of this engine is developed in the Matlab/Simulink computing environment, where simulations are performed in order to obtain suitable operation conditions and predict the performance of this machine. Cycle averaged simulations results provide an understanding of how operational parameters impact system performance. Intracycle simulation results based on a suitable operational data set highlight the instantaneous evolution of pressures, mass flow rates and forces acting on the liquid piston. For the chosen data set, the theoretical net mechanical power produced by the system is about 1.17 kW with a theoretical efficiency of 34% for a maximum pressure of 2.5 bar. Highlights: A free liquid piston Ericsson engine is presented. This system may be relevant for the conversion of medium temperature heat sources. A system with a U-tube of 0.175 m and a maximum stroke of 0.3 m is modeled. For a hot source of 360 °C, the operating frequency is 3.2 Hz. The simulation predicts a power of 1.17 kW and an efficiency of 34%.